Business process management – a construction case study. Issue 1 (3rd January 2017) - Dave, Bhargav
Abstract : Purpose: This paper aims to demonstrate the need for a structured business process improvement effort needed while restructuring organisational processes within a construction company. Through the longitudinal study, the study also highlights the importance of a continuous improvement initiative to sustain such an improvement effort. Design/methodology/approach: The research followed an action research and the case study approach using semi-structured interviews and group workshops within the case organisation. Overall, six departments were analysed, 35 interviews with senior and middle managers were conducted, existing business process documents were studied and processes were documented. The data were compiled using a process modelling software and Business Process Markup Notation methodology. Additionally, a longitudinal analysis following the completion of process modelling exercise was carried out over a period of eight years. Findings: The overall study highlights the importance of business process management (BPM) for construction organisations. The case study also demonstrated that even smaller business units and its processes affected the overall value chain in a major way and the importance to analyse the process interdependencies between organisational units. Research limitations/implications: The main limitation of the research was that it is based on a single-case-study company based in the UK. More research is needed with other organisations with different work practices and culture and geographic location. Practical implications: Primarily, the research outlines specific steps taken during a structured process improvement exercise in a construction company, including procedures for collecting data, developing process maps and analysis of data. The longitudinal study highlights the challenges in sustaining such an initiative. For practitioners, strengths and weaknesses of various process improvement methods and a detailed description of a BPM implementation can be used as a guideline for future projects. From a research point of view, the paper highlights the need for deeper and long-term analysis of such initiatives and the importance of immersion of researchers within the environment. Originality/value: The paper provides deeper insights into the structured process improvement exercise within a construction company. Second and more importantly, the longitudinal study is one of its kind in the construction industry to shed light on the factors affecting sustainability of such initiatives.